(untitled) (European Journal of Emerging Technology and Discoveries, 2025)
Based on the results of the theoretical research, the purpose of the experimental research is to determine the torques, rotation frequencies and noise on the drive and intermediate shafts in the copy of the S2U-160 brand reducer. This article is dedicated to the design and experimental research results of a two-stage compound helical gear mechanism with an elastic element. Helical gear mechanisms are widely used in industries to reliably transmit rotational motion under high loads while maintaining efficiency and stability. The use of elastic elements in these mechanisms helps to improve their dynamic characteristics by reducing vibrations and dynamic loads. The study examines the impact of elastic elements on the performance of the gear system. Throughout the experiments, changes in key parameters such as the angular displacement, angular velocity, and torque of the mechanism were observed. Additionally, the stability of the system’s dynamics and the reduction of vibrations were evaluated. These types of mechanisms are widely used in cotton processing plants as well as in other industries with high-load demands. The inclusion of elastic elements enhances the lifespan and efficiency of the mechanism. The results obtained in this study demonstrate the benefits of applying elastic elements in mechanical transmissions for improving the durability and load-bearing capacity of the gear wheels. Moreover, the findings suggest new opportunities for the efficient application of elastic components in various industrial mechanical systems. The study confirms that by using elastic elements, dynamic loads can be reduced, leading to greater durability and performance of the helical gear mechanism.